ChemInform Abstract: Transition Metal Complexes Containing Dihydrogen Hypodiphosphate in Eclipsed Conformation as Ligand: Preparation, Crystal Structure, Vibrational Spectra, and Thermal Behavior of K2 [M(H2P2O6)2 (H2O)2]·H2O (M: Co, Ni, Cu, and Zn). Issue 16 (22nd April 2014) - Gjikaj, Mimoza; Wu, Peng
Abstract The title compounds are prepared by simple reaction of MCO3 (M: Co, Ni, Cu, and Zn), H4P2P6, and KOH in aqueous solution at room temperature.